On the economics of social innovation – a conceptual framework and its policy implications. Issue 4 (1st October 2020) - Cuntz, Alexander; Foray, Dominique; Mostovova, Elena
ABSTRACT: Social innovations addressing social, economic and environmental challenges are increasingly recognized as crucial drivers of social changes and today represent an important target for innovation and related policies on national and international levels, including the United Nations' Sustainable Development Goals (SDG). However, the concept of social innovation remains vague. This paper builds a conceptual framework from an economic perspective: The main criterion for identifying a social innovation concerns the way the benefits generated by an innovation are distributed between the (private or public) innovator and society. We close the paper by an extensive discussion of the conceptual boundaries, the research agenda and the policy implications we can derive based on the framework.